IT’S MODY! NOT TYPE 2 DIABETES - Loh, Chiew Wah; Selveindran, Nalini M; Hong, Janet YH; Ong, Jayne AX; Morthy, Sasirekha K (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND MODY (maturity-onset diabetes of the young) is a rare form of diabetes which represents a clinically heterogeneous group of autosomal-dominant disorders caused by mutation in genes involved in beta cell development and insulin secretion. The classic phenotype of MODY includes nonketotic noninsulin-dependent diabetes with diagnosis before age 25 years and an affected parent. However, there is clinical overlap between MODY, type 1, and type 2 diabetes resulting in frequent misdiagnosis of MODY. Data collection was done by reviewing the electronic medical records of the selected patient and salient points were noted. CASE TSE, presented at the age of 9 years old with hyperglycaemia detected on routine monitoring. On presentation, she was asymptomatic and her investigations revealed nonketotic hyperglycaemia (RBS 10.5 mmol/L). Clinically there was no evidence of acanthosis nigricans and her BMI was within normal range. Further investigations revealed HbA1c of 8.6% with an abnormal OGTT (FBS: 8.9 mmol/L, 2 hours post: 20.97 mmol/L). Her pancreatic autoantibodies came back as all negative and had a high c-peptide level of 357.9 pmol/L. She was treated initially with oral metformin. On further history, the mother had early-onset diabetes and there was a strong family history of early-onset diabetes on the maternal side. Genetic testing by whole exome sequencing revealed a heterozygous variant in HNF1B. She was further investigated and renal function, lipid profile and ultrasound of the abdomen and kidneys were normal. She was subsequently transitioned to insulin therapy. CONCLUSION HNF1B has a wide phenotypic spectrum, and affected individuals may present with isolated renal disease, isolated diabetes, or both. This case highlights the importance of the precision medicine approach in MODY. Molecular genetic testing can identify the subtypes and has profound implications on diabetes treatment and prediction of future development of co-morbidities, allowing early preventive or supportive treatment.